The Effects Of Acute Kidney Injury On The Outcomes Of Patients With Gastrointestinal Bleeding - Mahvesh Mahmud; Khurram Baqai; Ashok Kumar (Journal of Rawalpindi Medical College)
Objective: To determine the clinical outcomes of patients with acute kidney injury in patients with upper gastrointestinal bleeding (UGIB), as it is a very frequently encountered condition with high morbidity and treatment costs. We aimed to study the differences in clinical outcomes in patients with UGIB who developed acute kidney injury (AKI) and those who did not.